Reviewing the Global Smartphone Industry Strategic Implication in Response to COVID-19 Situation - Alam, Samsul (International Journal of Interactive Mobile Technologies (iJIM), 2021)
The global smartphone brands were progressing aggressively over time. A sudden unexpected turbulent situation known as a global pandemic declared by the World Health Organization (WHO) about a century later in the history of human civilization stops this progress. It makes the industry bound to fall behind. This study aims to review and analyze the impact of the present pandemic situation due to Coronavirus Disease 2019 (COVID-19) on the global smartphone industry. It shows its competitive scenarios focusing on smartphone demand and supply. Thus, the study suggest a strategic approach to combat this situation. It is done by reviewing the latest literature published explicitly in 2020. The findings of this study reveal a significant negative impact of COVID-19 on global smartphone brands, primarily especially in the big markets of this industry, namely China, India, USA, Europe. Conversely, it can also positively impact the industry, especially in some developing countries. The positivity is seen due to the expanded demand for smartphones in some sectors like education, business, and entertainment media shifted online, triggering the user’s need to purchase a new smart device. Lastly, based on the understanding of the current scenario, some strategic approaches are discussed, and appropriate solutions are given for the industry to cope up with the pandemic crisis and, at the same time, how to attain success. The strategic directions given at the end can be applied to the industry’s sustainability and growth.